Motivasi Peternak dalam Budidaya Sapi Potong Madura di Desa Dempo Barat Kecamatan Pasean Kabupaten Pamekasan - Ira Khanitaturrahmah; Amanatuz Zuhriyah; Mardiyah Hayati (AGRIMOR, 2022)
Dempo Barat Village is one of the villages in the Pamekasan Regency, which is a native Madura cattle development area with sonok, frequent, and beef cattle. Breeders typically use the money they save from Madura beef cattle maintenance to cover living expenses, school expenditures, or start-up costs. A study was undertaken to analyze the motivation of beef cattle farmers in West Dempo Village with the goal of determining the degree of farmer motivation and the factors that influence farmer motivation in order to increase the Madura beef cattle farming industry in West Dempo Village. The method utilized in this study was descriptive quantitative, with multiple linear regression analysis used to analyze the degree of motivation of farmers and the factors that influence their motivation. According to the findings of this survey, the majority of farmers' motivation levels are moderate, with a percentage of 83.7 percent. The social environment of farmers has a major impact on their motivation, although other characteristics such as age, education, experience, and the number of cows have no impact on their motivation.